Profil Pemahaman Guru PAI dan Non PAI Tentang Manajemen Sekolah Menengah Atas - Sabanah, Imas; Muharam, Asep; Rochman, Chaerul; Nurmila, Nina (Universitas Negeri Surabaya, 2022)
Education is an activity, which is very important for all humans, with human education it can change behavior and knowledge for the better. The achievement of educational programs through educational and learning measures is strongly influenced by various variables, one of which is the adequate accessibility of school personnel in addition to ideal use. The existence of these students is very important to help complete the path to school administration. Each training unit is responsible for building the abilities and talents of students to become proficient, and talented as mandated by law. With the aim that students meet assumptions can be made according to their wishes and abilities. The method used in this study was a survey, while the data collection technique used in this study used an instrument in the form of a questionnaire. Based on the results of research on school management that the average understanding of teachers, both Islamic Education teachers and Non Islamic Education teachers, shows that teachers understand all statements well, but of the five statements there is the lowest average, namely statement 3 with a mean of 4. Statement 3 is